No highway in the sky [videorecording (DVD)] - Stewart, James, 1908-1997; Dietrich, Marlene; Shute, Nevil, 1899-1960 (20th Century Fox Home Entertainment, 2013)
An aeronautical engineer predicts a new type of airplane will fail after a certain amount of time in the air, and then finds himself onboard one of the doomed planes while headed to a crash site.